Faktor-Faktor Mempengaruhi Lama Migran Menetap yang Bekerja pada Sektor Informal di Kota Palembang - Hertian Nova; Fauziah Asyiek; Happy Warsito (Jurnal Empirika, 2017)
This study aims to examine the factors that influence long settled migrants who work in the informal sector in Sub Ilir Timur II Palembang. In addition, to determine the factors that affect the long migrants settled in the district of East Ilir II, Palembang.  The research method is descriptive quantitative research which was analyzed by using multiple regression estimation techniques with the least squares method (OLS). Data or information was collected through questionnaires and interviews which may include factors affecting long settled migrants who work in the informal sector in Sub Ilir Timur II Palembang. The data were analyzed through F test to test the overall variables (partial) and t test to test variables simultaneously. Furthermore, to determine the most influential and insignificant variables, stepwise regression method was used. Thus, it was found that the most influential variable of the length of settled migrants is income variable, where the income in the the area of destination is greater than the income in their area of origin. Furthermore, the variable of lack of employment in the area of origin is the most influential variable for the driving factors from the area of origin which affects to the high willingness of people to migrate and seek employment opportunities in the the area of destination. So it can be assumed that as long as the income in the the area of destination larger than that in the area of origin and there is no enough jobs available and desirable in the areas of origin of the migrants, accordingly, the migrants will stay longer in the the area of destination.